Enhancing Fire Safety in Multiple-Level Basements: Utilizing Computational Tools for Smoke Management - Duc T. Le; Tri Minh Nguyen; Yen H.P Duong; Tan M. Le; Viet T. Tran (Chemical Engineering Transactions)
The process of ensuring basement airflow and explosion safety is currently a critical concern. Designing a smoke management system for a multi-story basement poses a significant challenge for engineers because the basement is located underground, making natural ventilation through openings nearly impossible. Furthermore, the placement of stacking vehicles in the basement increases the risk of fire and smoke spread due to the high density of vehicles in a limited area. To address these challenges, Fire Dynamics Simulation (FDS), a Computational Fluid Dynamics (CFD) tool, was chosen to provide solutions for the combustion process and to predict risks. FDS enables the visualization and prediction of fire scenarios on a large scale without compromising safety or requiring substantial investment. This research aims to predict the efficiency of smoke management in a level-2 basement containing two car stackers in an actual office building in Melbourne, Australia. The model incorporates Very-Large Eddy Simulation (V-LES) for turbulence, with fire modeled using the Heat Release Rate (HRR) of 15 MW and an ultrafast T-square fire growth. The study examines the performance of the smoke management system by considering different criteria relating to temperature, visibility and toxic gas level with an exhaust fan capacity of 4 m3/s under two scenarios: successful activation of the sprinkler system and failure to activate the sprinkler system. The obtained results show a requirement of better smoke management system in the structure due to the risks to human life in both scenarios.